THE ROLE AND IMPORTANCE OF DIGITAL TECHNOLOGIES IN IMPROVING BUSINESS PROCESS ORGANIZATION STRATEGIES - Nutfulloev Tolib (Modern American Journals, 2025)
In recent years, the rapid advancement of digital technologies has transformed the strategic landscape of business process organization. This paper investigates the impact of digital tools such as artificial intelligence (AI), big data analytics, cloud computing, and the Internet of Things (IoT) on business process efficiency and competitive advantage. Using econometric analysis and data from 300 enterprises, the study provides quantitative insights into the productivity gains, cost savings, and operational improvements facilitated by digital adoption. Results indicate that businesses with a strategic focus on digital integration are better positioned for agility and sustained growth. The findings underscore the need for digital competency within teams and tailored digital investment strategies.
Keywords: Digital technologies, business process organization, strategy improvement, econometric analysis, AI, cloud computing, productivity